2017
DOI: 10.1049/mnl.2016.0687
|View full text |Cite
|
Sign up to set email alerts
|

The design and microfabrication of a sub 100 mg insect‐scale flapping‐wing robot

Abstract: A piezo-actuated self-lifting insect inspired flapping-wing robot is presented. A novel method is presented in the work, which has taken into account the difficulties and the precision of assembly among micro components. Each component is properly designed and reasonably arranged to reduce the assembly difficulties of such insect-scale robot. Specifically, the design of the piezoelectric actuator has taken into account the electrical isolation and assembly issues. The transmission and the airframe are integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…In addition, the rapid development of MEMS boosts the born of tiny bio‐mimicking flapping‐wing MAV that is close to the scale (or even at the same scale) of real insects [28, 29], as listed in Fig. 5.…”
Section: Bio‐inspired Mavsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the rapid development of MEMS boosts the born of tiny bio‐mimicking flapping‐wing MAV that is close to the scale (or even at the same scale) of real insects [28, 29], as listed in Fig. 5.…”
Section: Bio‐inspired Mavsmentioning
confidence: 99%
“… Bio‐mimicking flapping‐wing MAVs close to insect scale (a) Robobee from Harvard University [28], (b) the Piezoelectric‐actuated MAV from Shanghai Jiao Tong University [29], (c) RoboFly from University of Washington [30]…”
Section: Bio‐inspired Mavsmentioning
confidence: 99%
“…However, limited by the size of the motor and the complex transmission, these FMAVs weigh around 20 g with the size close to the human palm, which is far more than real insects. To be more similar to insects, some researchers have been focusing on the research of the insect-scale tailless FMAVs and several studies have successfully demonstrated liftoff [8][9][10][11][12] . Unlike the rotary displacement output of the motor, these insect-scale FMAVs use reciprocating actuators to mimic the contraction of insect muscles, which can realize the flapping of the wings through a simpler transmission mechanism [8,[10][11][12] or even without transmission [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al [14] proposed a precision position stage with a piezoelectric actuator. In addition, Zou et al [15] developed an insect-scale flapping-wing robot with a wingspan of 35 mm. The robot had piezoelectric actuators.…”
Section: Introductionmentioning
confidence: 99%